Poligami dan Kaitan dengan Nikah Sirri (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2022)
Marriage is something that is very important in human life, therefore a marriage must be in accordance with religious provisions and laws and regulations so that the marriage gets legal certainty and protection. Polygamy is basically permissible in Islam, which however has rules that must be obeyed, namely: a husband may marry women he likes, but do not let four wives leave, other than that it is obligatory to harm them fairly, provide external maintenance (basic food, daily underwear) and spiritual maintenance. However, currently in society it is common for a man to marry for the second time or polygamy by way of sirri marriage, sirri marriage is legally valid according to the Islamic religion which has been regulated in legislation, and also sirri marriage is illegal because it does not have the power law. A first wife can demand the annulment of a marriage to the Syar'iyah Court because the husband has committed polygamy in a sirri marriage without the consent of the first wife and the husband can be subject to criminal sanctions in the form of a maximum prison sentence of 7 years according to Article 279 of the Criminal Code and a maximum fine of up to high Rp. 7,500, - according to Article 45 PP No. 9 of 1975.
Keywords: Marriage; Polygamy; Sirri